Accumulated common variants in the broader fragile X gene family modulate autistic phenotypes. Issue 12 (26th November 2015) - Stepniak, Beata; Kästner, Anne; Poggi, Giulia; Mitjans, Marina; Begemann, Martin; Hartmann, Annette; Van der Auwera, Sandra; Sananbenesi, Farahnaz; Krueger‐Burg, Dilja; Matuszko, Gabriela; Brosi, Cornelia; Homuth, Georg; et al.
Abstract: Fragile X syndrome (FXS) is mostly caused by a CGG triplet expansion in the fragile X mental retardation 1 gene ( FMR1 ). Up to 60% of affected males fulfill criteria for autism spectrum disorder (ASD), making FXS the most frequent monogenetic cause of syndromic ASD. It is unknown, however, whether normal variants (independent of mutations) in the fragile X gene family ( FMR1, FXR1, FXR2 ) and in FMR2 modulate autistic features. Here, we report an accumulation model of 8 SNPs in these genes, associated with autistic traits in a discovery sample of male patients with schizophrenia ( N = 692) and three independent replicate samples: patients with schizophrenia ( N = 626), patients with other psychiatric diagnoses ( N = 111) and a general population sample ( N = 2005). For first mechanistic insight, we contrasted microRNA expression in peripheral blood mononuclear cells of selected extreme group subjects with high‐ versus low‐risk constellation regarding the accumulation model. Thereby, the brain‐expressed miR‐181 species emerged as potential "umbrella regulator", with several seed matches across the fragile X gene family and FMR2 . To conclude, normal variation in these genes contributes to the continuum of autistic phenotypes. Synopsis: Based on a novel approach, phenotype‐based genetic association study, first evidence is provided that a particular constellation of completely normal genotypes in the "broader fragile X gene family" contributes to autistic phenotypes. An accumulation model of 8 SNPs from the broader fragile X gene family ( FMR1, FXR1, FXR2, and FMR2 ) is associated with autistic traits in a discovery sample of male schizophrenia patients as well as three independent replication samples of neuropsychiatric patients or general population. The underlying novel approach, named phenotype‐based genetic association study (PGAS), may serve as universal guide in the exploration of genotype contributions to quantifiable phenotypes. Comparing peripheral blood mononuclear cells of extreme group subjects with high versus low genetic risk by small RNA sequencing revealed quantitative differences in the brain‐expressed miR‐181 family, which has several seed matches across the broader fragile X gene family. Future studies based on extensive in vivo work in animal models are needed to delineate how and when the miR‐181 family may act as an overarching modulator of the fragile X genes. Abstract : Based on a novel approach, phenotype‐based genetic association study, first evidence is provided that a particular constellation of completely normal genotypes in the "broader fragile X gene family" contributes to autistic phenotypes.